GEOLOGICAL BEHAVIOUR OF ROCK MASSES IN UNDERGROUND EXCAVATIONS - Marinos, P. V (Bulletin of the Geological Society of Greece, 2010)
The paper deals with the engineering geological behaviour of rock masses in underground excavations. In general, the application of the well-known classification systems has the drawback of not displaying necessary information concerning the behaviour of rock masses, especially the weak ones, in tunnelling. Consequently, there are many cases in which the geological “identity” of the geomaterial is lost since it is not involved in the analysis. In that way it is possible that its special characteristics are mislaid. Within this framework, a system for assessing the failure type mechanisms of the rockmass (i.e. deformation due to overstressing, overbrakes or wedge failure, “chimney” type failure, ravelling ground) for unsupported tunnel-section is presented. These parameters, used for this system, are the structure of the rockmass, the intact rock strength and the overburden thickness. The experience gained by the recent tunnelling construction in the Greek territory, under particularly difficult geological conditions, provided excellent and numerous data for this study.